The impact of community older adult care services on the quality of life of older adults in China: the mediating role of social adaptation - Yuanfeng Liu; Shilin Yang (Frontiers in Public Health)
BackgroundWith the deepening trend of aging in China, community older adult care services occupy an important position in China’s older adult care system. This paper aims to explore the impact of different types of community older adult care services on the quality of life of older adults and to analyze its underlying influencing mechanism.MethodsThe research data are obtained from the 2020 China Longitudinal Aging Social Survey data. The Structural Equation Model is used to examine the relationship between of three types of community older adult care services on older adults’quality of life.Results(1) Three types of community older adult care services are positively associated with quality of life of older adults. Compared to basic older adult care services, extended older adult care services have a more significant impact on older people’s quality of life. (2) It is found that the impacts of three types of community older adult care services on the quality of life of older adults are heterogeneous in terms of age, registered residence, and disablement status. (3) Social adaptation mediated the relationship between three types of community older adult care services and older adults’ quality of life.DiscussionThe results of this study show that three types of community older adult care services could improve the quality of life of older adults, and social adaptation plays a mediating role between three types of community older adult care services and quality of life. Therefore, it is necessary to strengthen the supply of community older adult care services, especially extended older adult care services. By accurately identifying the needs of the older adults and optimizing service supply, giving the older adults more useful services, improving their attitudes towards society and helping them better adapt to society, thereby improving the quality of life of older adults. This study provides a basis for optimizing community older adult care services and improving the quality of life of the older adults, and emphasizes the key role of social adaptation, which has important practical guiding significance for promoting the sustainable development of the older adult care service system.